Microemulsion: A Review - Sharma, Neha; V, Antil; Jain, S (Asian Journal of Pharmaceutical Research and Development, 2013)
Microemulsions have emerged as novel vehicles for drug delivery which allow sustained or controlled release for percutaneous, peroral, topical,transdermal, ocular and parenteral administration of medicaments. They offer the advantage of spontaneous formation, ease of manufacturing and scale-up, thermodynamic stability, improved drug solubilization of hydrophobic drugs and bioavailability. This article focuses on types of microemulsion, composition of microemulsion, preparation & evaluation of microemulsion,While microemulsions are used in several fields, this article focuses on the reported investigations for different applications.